Detraining Differentially Preserved Beneficial Effects of Exercise on Hypertension: Effects on Blood Pressure, Cardiac Function, Brain Inflammatory Cytokines and Oxidative Stress - Agarwal, Deepmala (Public Library of Science, 2012)
AIMS: This study sought to investigate the effects of physical detraining on blood pressure (BP) and cardiac morphology and function in hypertension, and on pro- and anti-inflammatory cytokines (PICs and AIC) and oxidative stress within the brain of hypertensive rats. METHODS AND RESULTS: Hypertension was induced in male Sprague-Dawley rats by delivering AngiotensinII for 42 days using implanted osmotic minipumps. Rats were randomized into sedentary, trained, and detrained groups. Trained rats underwent moderate-intensity exercise (ExT) for 42 days, whereas, detrained groups underwent 28 days of exercise followed by 14 days of detraining. BP and cardiac function were evaluated by radio-telemetry and echocardiography, respectively. At the end, the paraventricular nucleus (PVN) was analyzed by Real-time RT-PCR and Western blot. ExT in AngII-infused rats caused delayed progression of hypertension, reduced cardiac hypertrophy, and improved diastolic function. These results were associated with significantly reduced PICs, increased AIC (interleukin (IL)-10), and attenuated oxidative stress in the PVN. Detraining did not abolish the exercise-induced attenuation in MAP in hypertensive rats; however, detraining failed to completely preserve exercise-mediated improvement in cardiac hypertrophy and function. Additionally, detraining did not reverse exercise-induced improvement in PICs in the PVN of hypertensive rats; however, the improvements in IL-10 were abolished. CONCLUSION: These results indicate that although 2 weeks of detraining is not long enough to completely abolish the beneficial effects of regular exercise, continuing cessation of exercise may lead to detrimental effects.